Implementasi Program Santri Husada Dalam Upaya Kemandirian Pesantren Bidang Kesehatan di Pondok Pesantren Riyadlotut Thalabah Sedan Rembang - Mardliyah, Ikhda Khullatil; Rusli, Moch; Purwanti, Sri (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Health problems in Islamic boarding schools are very diverse, such as infectious diseases, non-communicable diseases, and emergencies that can occur at any time. Regarding infectious diseases, some Islamic boarding schools fall into the risky category because they are communal and densely populated places to live. Therefore, it is necessary to have promotive and preventive efforts to prevent the spread and transmission. Pesantren efforts that are carried out to promote health in Islamic boarding schools include the development of Islamic boarding schools in the health sector to the formation of Poskestren (Pesantren Health Posts), because health is a problem that should not be underestimated but must really be a point that should be considered regularly. Riyadlotut Thalabah Islamic Boarding School is one of the Islamic boarding schools in Central Java which has had a poskestren since 2018 and has activated health education and formed a